TINJAUAN YURIDIS TERHADAP KETENTUAN PASAL 3 UNDANG- UNDANG NOMOR 1 PENETAPAN PRESIDEN TAHUN 1965 TENTANG PENCEGAHAN PENYALAHGUNAAN DAN PENODAAN AGAMA - Wati, Irena; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In the development of society almost throughout Indonesia, there were not a few deviant sect or organizations trust or public beliefs which contradicted the teachings and laws of religion. Adherents of these deviant sect have caused many things that violate the law, break national unity and tarnish religion. To prevent the prolongation of these actions which could endanger the unity of the Nation and the State, the Presidential Decree was issued. However, the existence of the Presidential Decree which has become the Law which contains provisions on sanctions for perpetrators of deviations from religious teachings often sanctions given are not in accordance with the legal provisions that should be. The existence of Law Number 1 of the Presidential Decree of 1965 concerning Prevention of Abuse and Blasphemy of Religion which contains provisions on administrative law and at the same time criminal law by including Article 156a of the Criminal Code in the Blasphemy Law. However, the existence of a criminal as an alternative sanction (Ultimum remedium) is ignored in the provision of sanctions in perpetrators of deviations from religious teachings. The purpose of writing this essay, namely; First, to find out the juridical review of the provisions of Article 3 of Act Number 1 of the Presidential Decree of 1965 concerning Prevention of Abuse and Blasphemy of Religion, Second; To find out the principle of ultimum remedium based on law enforcement of criminal acts against religion contained in Article 3 of Act Number 1 of the Presidential Decree of 1965 concerning Prevention of Abuse and Blasphemy of Religion, Third; To find a solution to the problem of criminal acts against religion in Article 3 of Act No. 1 of the Presidential Decree of 1965 concerning Prevention of Abuse and Blasphemy of Religion.This type of research can be classified into a type of normative juridical research. this research was conducted by examining secondary data and approaches to law, this normative research examines the legal principles of reasons that can eliminate criminality. The data sources used are, primary data, secondary data, tertiary data, data collection techniques in this study are normative juridical, the data used is library research.From the results of the problem research there are four points that can be concluded. First, law enforcement by means of reason and non-reasoning. Second, the criminalization policy. Third, government policies in prevention, enforcement and law enforcement policies. Fourth, reinterpretation, reformulation or revision of the provisions of blasphemy. In order to create a fair state and guarantee legal certainty to protect religious security based on their respective beliefs that have been recognized in Indonesia.Keywords: Crime Against Religion, Law Enforcement, Criminalization, Reformulation, State of Law